Proton pump inhibitor‐induced large gastric polyps can regress within 2 months after discontinuation: Experience from two cases - Tomoki Inaba; Kenji Yamauchi; Shigenao Ishikawa; Hugh Shunsuke Colvin; Koichi Izumikawa; Kumiko Yamamoto; Sakuma Takahashi; Masaki Wato; Satoko Nakamura; Seiji Kawano (DEN Open)
Abstract The long‐term use of proton pump inhibitors (PPIs) can induce fundic gland polyps (FPs) in the stomach, sometimes leading to numerous large FPs (LFPs). Although PPI discontinuation can reduce LFP size and number, the underlying process remains unstudied. A 63‐year‐old woman on esomeprazole (20 mg daily for 10 years) was scheduled for endoscopic LFP removal. After PPI discontinuation, her LFPs regressed to <10 mm within 35 days. A 60‐year‐old male physician on rabeprazole (10 mg daily for 12 years) had LFPs detected via esophagogastroduodenoscopy screening. He opted for weekly esophagogastroduodenoscopy with pathological evaluations to monitor changes post‐discontinuation. One week after PPI withdrawal, gastric juice acidity and viscosity increased, with erosion observed on nearly all LFP surfaces. By day 35, all LFPs regressed and resembled sporadic FPs. This study demonstrated that PPI‐induced LFPs regress within a short period post‐discontinuation and suggests that LFP volume reduction is linked to gastric environment changes, particularly increased acidity.